Surface Free Energy of Titanium Disks Enhances Osteoblast Activity by Affecting the Conformation of Adsorbed Fibronectin - Lin, Jiating; Dong, Hao; Wen, Yin; Zhuang, Xianxian; Li, Shaobing (Frontiers in Materials, 2022)
This study evaluated the influence of surface free energy (SFE) of titanium disks on the adsorption and conformation of fibronectin (FN) and the biological behavior of osteoblasts cultured on the FN-treated modified surfaces. High [H]-SFE titanium disks were irradiated by a 30 W UV light, while low (L)-SFE titanium disks received no treatment. The surface characteristics of the titanium disks were examined using scanning electron microscope, optical surface profilometer, X-ray photoelectron spectroscopy, and contact angle measurements. Adsorbed FN on different groups was investigated using attenuated total reflection-Fourier transform infrared spectroscopy. MG-63 cells were cultured on FN-treated titanium disks to evaluate the in vitro bioactivity. The experiment showed H-SFE titanium disks adsorbed more FN and acquired more β-turn content than L-SFE group. MG-63 cells cultured on FN-treated H-SFE titanium disks showed better osteogenic responses, including adhesion, proliferation, alkaline phosphatase activity and mineralization than that on FN-treated L-SFE titanium disks. Compared to L-SFE titanium disks, integrin-β1, integrin-α5 and Rac-1 mRNA levels were significantly higher in MG-63 cells on FN-treated H-SFE after 3h of culture. These findings suggest that the higher SFE of H-SFE compared to L-SFE titanium disks induced changes in the conformation of adsorbed FN that enhanced the osteogenic activity of MG-63 cells.